2018
DOI: 10.1177/0961000618788725
|View full text |Cite
|
Sign up to set email alerts
|

The adoption of Web 2.0 technologies in academic libraries: A comparative exploration

Abstract: This paper addresses the adoption and non-adoption of communication methods such as social media and explores the implementation of Web 2.0 technologies and their use in academic libraries. I interviewed 16 library employees from six academic university libraries in the Flanders region of Belgium and in South Africa. I explored five academic university libraries in the urban regions of Flanders and South Africa and one situated in a rural region of South Africa. This article discusses the benefits of using soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Adewojo and Mayowa-Adebara (2016) lament the lack of management support as it significantly contributed to non-use of social media tools among academic librarians in Nigeria. Williams (2020) makes similar observations about a lack of management support deterring effective social media adoption in Belgian and South African university libraries. Mishra (2008) strongly recommends that management commits to the adoption of social media applications and at the same time also becomes the front runners in the use of social media tools.…”
Section: Literature Reviewmentioning
confidence: 58%
See 2 more Smart Citations
“…Adewojo and Mayowa-Adebara (2016) lament the lack of management support as it significantly contributed to non-use of social media tools among academic librarians in Nigeria. Williams (2020) makes similar observations about a lack of management support deterring effective social media adoption in Belgian and South African university libraries. Mishra (2008) strongly recommends that management commits to the adoption of social media applications and at the same time also becomes the front runners in the use of social media tools.…”
Section: Literature Reviewmentioning
confidence: 58%
“…Akporhonor and Olise (2015, p. 6) decry Nigerian universities' lack of commitment towards supporting the adoption of social media tools by academic librarians. Williams (2020), Adewojo and Mayowa-Adebara (2016), Kumar (2015) and Khan and Bhatti (2012) reported that inadequate funding for libraries had prevented some academic libraries from deploying certain social media tools especially those that would require funds to do so. Mosha et al (2015) submit that the high cost of internet connectivity also contributes towards low usage of social media tools.…”
Section: Academic Librarians In Zimbabwementioning
confidence: 99%
See 1 more Smart Citation
“…Although, despite critics that reference the inefficiency of social media use among libraries ( Magoi et al, 2017 ), it is evident that these tools have become a means for institutions to communicate with and meet the information needs of users ( Ofili & Emwanta, 2014 ). Plus, innovative digital tools encourage younger generations to access library services ( Williams, 2018 ), which is why university libraries need to participate in creating their online social reality ( Garofalo, 2013 ). Effectively using social media is also seen as a critical 21st-century skill expected of academic library staff ( Chawner & Oliver, 2013 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2021), is to include patrons in information literacy activities and/or training(Giray & Oare, 2018;Williams, 2020). Additionally, Giray and Oare (2018) noted how crucial it is for institutions to succeed in transitioning from their conventional roles to information commons that librarians get training in communication skills.…”
mentioning
confidence: 99%